COMPARISON OF FEED CONVERSION RATIO (FCR) OF TILAPIA AND CATFISH IN MAGGOT-BASED AQUAPONIC CULTIVATION SYSTEM - Nurdiana Nurdiana; Nursyahran Nursyahran; Heriansah Heriansah; Ardi Eko Mulyawan (Institut Teknologi dan Bisnis Maritim Balik Diwa, 2026)
This study compared the Feed Conversion Ratio (FCR) of Nile tilapia (Oreochromis niloticus) and African catfish (Clarias sp.) cultured in a maggot-based aquaponic system. The experiment was conducted from March to May 2025 using a completely experimental approach with two treatments and three replications. Nile tilapia and African catfish were fed dried Black Soldier Fly (Hermetia illucens) larvae as the sole protein source, while mustard greens were cultivated as the plant component of the aquaponic system. Feed utilization efficiency was evaluated using Feed Conversion Ratio (FCR), and differences between treatments were analyzed using an independent-samples t-test. The results demonstrated that Nile tilapia exhibited a significantly lower FCR (0.41) than African catfish (0.70), indicating superior feed utilization efficiency. Statistical analysis confirmed a significant difference between the two treatments (p = 0.037), suggesting that fish species significantly influenced the efficiency of maggot utilization under identical aquaponic conditions. The lower FCR observed in Nile tilapia was attributed to its omnivorous feeding behavior, greater digestive adaptability to insect-based diets, and better compatibility with the nutrient recycling processes occurring within the aquaponic system. Overall, the findings indicate that integrating Black Soldier Fly larvae with aquaponic technology can substantially improve feed efficiency while reducing production costs and nutrient waste. Nile tilapia demonstrated greater suitability than African catfish for sustainable maggot-based aquaponic production systems.